Sosialisasi Dampak Polusi Plastik terhadap Pariwisata sebagai Upaya Mendukung Pariwisata Berkualitas dan Berkelanjutan - Taufik, Muhammad; Muharis, Muharis; Anggara, Bagas; Sumardani, Rizki; Ramadani, Aisyah (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2025)
The rapid development of tourism has many negative consequences, one of which is the problem of waste. Plastic pollution has become a global issue whose impact is greatly felt in the tourism sector. Tourists are increasingly aware and concerned about environmental issues, and polluted destinations often lose their appeal. The purpose of this community service is to socialize the impact of plastic pollution on tourism to support quality and sustainable tourism. This workshop was held at Bumigora University in collaboration with the Sane Mare (a non-government organization). The approach used in this study is the community development method. There are three steps used in implementing activities, namely planning, implementation, and evaluation. This study found that this activity is critical in increasing student awareness of the impact of plastic pollution as a step in supporting sustainable tourism. A joint commitment is needed from the community, tourism actors, and the government to reduce the use of plastic, strengthen the waste management system, and encourage responsible tourism behavior because plastic waste pollutes the sea, rivers, and tourist attractions.